2017
DOI: 10.3847/1538-4357/aa8958
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the Pulsating Extremely Low-mass White Dwarf Precursor WASP 0247–25B

Abstract: We present an analysis of the evolutionary and pulsation properties of the extremely low-mass white dwarf precursor (B) component of the double-lined eclipsing system WASP 0247−25. Given that the fundamental parameters of that star have been obtained previously at a unique level of precision, WASP 0247−25B represents the ideal case for testing evolutionary models of this newly-found category of pulsators. Taking into account the known constraints on the mass, orbital period, effective temperature, surface grav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
(87 reference statements)
2
12
0
Order By: Relevance
“…Very interesting research about the evolutionary and pulsational properties of WASP 0247−25B, a pre-ELMV star component of the double-lined eclipsing system WASP 0247−25, was presented by Istrate et al (2017). Maxted et al (2013) provided fundamental parameters of this star at a unique level of precision.…”
Section: Elmv and Pre-elmv Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very interesting research about the evolutionary and pulsational properties of WASP 0247−25B, a pre-ELMV star component of the double-lined eclipsing system WASP 0247−25, was presented by Istrate et al (2017). Maxted et al (2013) provided fundamental parameters of this star at a unique level of precision.…”
Section: Elmv and Pre-elmv Starsmentioning
confidence: 99%
“…Maxted et al (2013) provided fundamental parameters of this star at a unique level of precision. By employing state-of-the-art evolutionary models that take into account rotational mixing and diffusion processes along with a comprehensive stability pulsation analysis, Istrate et al (2017) were able to find a stellar model that closely reproduces observed properties of the star such as stellar mass, orbital period, surface gravity, effective temperature, surface chemical composition, and also the pulsation periods detected in the star. This reinforces the validity of the pre-ELM WD models of Istrate et al (2016a) that incorporate rotational mixing.…”
Section: Elmv and Pre-elmv Starsmentioning
confidence: 99%
“…Córsico & Althaus 2014Istrate et al 2016b). Pulsations have been found in two of the SWASP EL CVn binaries: WASP 0247-25 (Maxted et al 2013;Istrate et al 2017) and WASP 1628+10 (Maxted et al 2014b). The pulsation periods are 5-10 minutes and the amplitudes ∼1-2 per cent of the pre-He-WD luminosity.…”
Section: Pulsationsmentioning
confidence: 99%
“…The many observational discoveries and measurements of pulsating stars in the parameter space of ELM and pre-ELM WDs has prompted extensive theoretical investigations into their driving mechanisms and asteroseismic interpretations (Córsico et al 2012Córsico & Althaus 2014aIstrate et al 2016bIstrate et al , 2017Fontaine et al 2017;Calcaferro et al 2017a,b;Sánchez Arias et al 2018).…”
Section: Introductionmentioning
confidence: 99%